Penentuan Lokasi Potensial Ekspansi Hokben Berbasis GIS Kota Depok - Wahyu Nauval Hafizh; Dwi Marsiska Driptufany; Fajrin Fajrin; Dwi Arini (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Business expansion is a strategic step undertaken by companies to increase profitability while broadening their market reach. Hoka Hoka Bento (HokBen) is one of the companies that consistently implements this strategy. This study aims to identify potential locations for new HokBen outlets in Depok City by utilizing Geographic Information Systems (GIS) and spatial analysis. Several parameters were considered, including proximity to commercial and entertainment centers, competitors, educational facilities, public facilities, road networks, population density, banking services, hotels, offices, residential areas, hospitals, existing stores, and places of worship. The analysis was conducted using Euclidean Distance, Buffering, Reclassification, and the Analytical Hierarchy Process (AHP) to determine the priority weights of each criterion. These weights were then integrated through the Weighted Overlay technique to produce a location suitability map. The findings reveal that the most influential factors are commercial and entertainment buildings (0.101), road networks (0.099), and educational facilities (0.092). The resulting suitability map highlights potential areas across Depok City, particularly in zones close to community activity centers. The results demonstrate that GIS-based multicriteria analysis is effective for mapping location suitability and identifying strategic zones for expansion. Therefore, this research contributes to supporting the company’s strategic decision-making through data-driven approaches while also enriching the academic field of business geography and urban planning. In addition, the outcomes can be applied as a reference model for other fast-food chains or retail industries planning spatially optimized expansion strategies in highly competitive urban environments.